STRUKTUR UPACARA DAN FUNGSI PERTUNJUKAN TARI ASYEIK DALAM PENGOBATAN DI DUSUN EMPIH KECAMATAN SUNGAI BUNGKAL KOTA SUNGAI PENUH - Bella Febriza; Nerosti Nerosti; Zora Iriani (SENDRATASIK UNP, 2018)
AbstractThis Article was aimped to describe and analyze of ceremonial structure and function of Asyeik dance on treatmen in Dusun Empih Kecamatan Sungai Bungkal Kota Sungai Penuh. Type of this study was qualitative with descriptive method. Instrument in this study was the researcher. Type of data were both primary and secondary. Technique of collecting data were done by using library research, observation, interview, documentation and data analysis. Result of this study showed that performance of Asyeik dance on treatmen could be seen the relationship between it’s part namely mintak aroh, mulua kejea, manggoa atau nyerau, merancoah limao, tango nitai, nyembuah, penampilan tari asyeik, masoak bumoi, mageh hulu balea makoa. The performance of this had dominant elements where each other has symbiotic relationship. The elements were a dancer, bilan salih, motion, floor pattern, custom and music. Asyeik dance was used as a tool of treatmen ritual in Dusun Empih Kecamatan Sungai Bungkal Kota Sungai Penuh to healed the society who suffered an extreme pain which could not be healed by medical treatmen. If the sufferer did not heal sooner, then this dance would be held as a medium of treatmen. Keywords:    Structure, Ceremony and Function, Performance of Asyeik Dance